2010
DOI: 10.1146/annurev.earth.031208.100032
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Climate Effects of Individual Tropospheric Aerosol Particles

Abstract: Aerosol particles in the atmosphere exert a strong influence on climate by interacting with sunlight and by initiating cloud formation. Because the tropospheric aerosol is a heterogeneous mixture of various particle types, its climate effects can only be fully understood through detailed knowledge of the physical and chemical properties of individual particles. Here we review the results of individual-particle studies that use microscopy-based techniques, emphasizing transmission electron microscopy and focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(178 citation statements)
references
References 156 publications
3
174
0
1
Order By: Relevance
“…Due to biomass combustion, the number of soot particles increases significantly, which can be revealed through the enhanced BC mass concentration, as discussed in the next paragraph. Soot pollutants can heat the atmosphere and affect the radiative effect of aerosols on the atmosphere [19,20]. It can be seen from Figure 3c that there was also significant diurnal change in RH before the haze event, but that RH remained at the high level of 60%-70% during the haze event of 11-13 June.…”
Section: Meteorological Conditions and Pollutant Concentrationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to biomass combustion, the number of soot particles increases significantly, which can be revealed through the enhanced BC mass concentration, as discussed in the next paragraph. Soot pollutants can heat the atmosphere and affect the radiative effect of aerosols on the atmosphere [19,20]. It can be seen from Figure 3c that there was also significant diurnal change in RH before the haze event, but that RH remained at the high level of 60%-70% during the haze event of 11-13 June.…”
Section: Meteorological Conditions and Pollutant Concentrationsmentioning
confidence: 97%
“…Furthermore, atmospheric radiation mechanisms and agricultural activities could also be affected by haze on regional and global scales. Soot particles play the role of an absorbent, which heats the atmosphere and cools the Earth's surface [16][17][18][19][20]. Experts have estimated that regional haze events in China could lead to a 5%-30% decrease in crop yields [21].…”
Section: Introductionmentioning
confidence: 99%
“…These soot particles were dominated by chain like aggregates of carbon bearing spheres. Various studies have reported that the morphology of carbonaceous particle originated from combustion processes varied from soot chains to complex structures, which depend on fuels, burning conditions and atmospheric processes (Cong et al, 2009;Pósfai and Buseck, 2010;Tumolva et al, 2010). These branched clusters results from the interconnection of often hundred of carbonaceous spherules which stick together through a combination of adhesive surface forces and partial coalescence which occur at high temperature common during combustion (Murr and Bang, 2003).…”
Section: Sem/edx Characterization Of Pm 25 Samplesmentioning
confidence: 99%
“…Therefore, it is important to identify the sources of aerosol particles present in the southeastern United States, as well as their size and mixing state in order to accurately assess their impact on aerosol direct and indirect effects Moise et al, 2015;Posfai and Buseck, 2010). 5 Mixing state is described in terms of external and internal mixtures: an external mixture consists of particles that contain only one pure species per particle, while an internal mixture describes particles that contain equal amounts of all chemical species (Ault and Axson, 2017;Posfai and Buseck, 2010;Riemer and West, 2013). The mixing states of ambient aerosol populations are complex and can vary as a function of size, altitude, and particle age (Fu et al, 2012;Healy et al, 2014a;Moffet et al, 2010b;Pratt 10 and Prather, 2010).…”
Section: Introductionmentioning
confidence: 99%